The Effect of Team Games Tournaments Cooperative Learning Model on Student Learning Outcomes in Pancasila and Civic Education Learning - Tri Supriandono; Mukhamad Murdiono; Agus Riyanto (JTP - Jurnal Teknologi Pendidikan, 2023)
This study aims to determine the effect of the Teams Games Tournament (TGT) cooperative learning model on student learning outcomes in Pancasila and Citizenship Education (PPKn). The TGT cooperative learning model aims to improve students' knowledge, abilities, and skills in a fun and competitive learning atmosphere. This study adopted a quantitative approach with a quasi-experimental pretest-posttest control group design. Participants were selected from class XI MM 1 (control group) and XI FKK (experimental group) at SMK Negeri 1 Cikedung, Indramayu Regency using purposive sampling. The sample consisted of 48 students, 29 in the experimental group and 19 in the control group. Data analysis used SPSS 22, with a learning achievement test instrument consisting of 20 items. The results of the analysis showed that the average score of the experimental group's student learning outcomes was 82.06, while the average score of the control group was 77.89, with the moderate control group category and the high experimental group. Testing the hypothesis using the t test produces t count <t table (1.039 <2.015) with a significance level of 0.025 so that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Consequently, there was a significant difference in the post-test results between the control and experimental groups. Thus, the TGT cooperative learning model has a positive effect on the learning outcomes of Pancasila and Citizenship Education (PPKn), especially regarding the system and dynamics of Pancasila democracy, so that the learning outcomes in the experimental group are high.